[OP.1C.11] INITIAL ORTHOSTATIC HYPOTENSION ASSOCIATED WITH THE USE OF ANTIHYPERTENSIVE DRUGS IS HIGHLY PREVALENT IN PATIENTS WITH UNEXPLAINED SYNCOPE. (September 2017) - Van Twist, D.J.L.; Dinh, T.; Bouwmans, E.M.E.; Kroon, A.A.
Abstract : Objective: The prevalence of initial orthostatic hypotension (IOH) as a cause of syncope is unknown. IOH is defined as a transient decrease in blood pressure (BP) within 15 seconds after standing of >40 mmHg systolic and/or >20 mmHg diastolic, with symptoms of cerebral hypoperfusion, but without sustained orthostatic hypotension (BP decrease >20/10 mmHg after 1–3 minutes of standing). We hypothesized that IOH is highly prevalent among patients with unexplained syncope and that it is often associated with the use of antihypertensive drugs. Design and method: We prospectively collected data from all outpatients that were evaluated in our syncope-unit between September 2015 and November 2016. All patients were evaluated by two syncope-experts (a cardiologist and either a neurologist or an internal/vascular medicine specialist) and underwent a standard diagnostic protocol, including echocardiography, electrocardiography, and laboratory testing, as well as a beat-to-beat BP measurement using a Nexfin device (BMEYE, The Netherlands). We measured hemodynamic changes after active standing, first after lying supine for >5 minutes and then after squatting for 30 seconds. Symptoms of cerebral hypoperfusion were noted. If considered clinically indicated long-term rhythm-monitoring, cardiac exercise test, head-up-tilt-table-testing, electroencephalography, or additional imaging was performed. Results: Beat-to-beat-BP data were available for 157 patients (mean age 61.1 ± 18.6 years, BP 137 ± 18/83 ± 10 mmHg, 57% female). Clinical diagnoses for the cause of syncope are shown in the Table. Upon active standing, 78 patients (49.7%) met the BP criteria for IOH (mean −47.2 ± 14.5/−29.0 ± 11.6 mmHg within 15 seconds after standing). Of those 78 patients, 15 patients had sustained orthostatic hypotension, 29 did not report symptoms of hypoperfusion, and in 19 patients history or additional tests revealed an alternative diagnosis. Two patients did not meet the BP-criteria, but history taking also indicated IOH. Thus, 17 patients (10.8%) were diagnosed with IOH, of whom 59% used antihypertensive drugs (mostly beta-blockers). The squatting-to-standing test (n = 107) did not increase the number of patients diagnosed with IOH. Conclusions: IOH is highly prevalent in patients with unexplained syncope and is associated with the use of antihypertensive drugs in the majority of patients. Figure. No caption available.